1999
DOI: 10.1177/019262339902700315
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Clinical Pathology Parameters During Gestation in the New Zealand White Rabbit

Abstract: Hematology and serum chemistry parameters were analyzed in 2 groups of pregnant rabbits to assess changes in these parameters over the course of gestation. These data were used to generate a historical control reference range for embryofetal development regulatory toxicology studies. During the 28-day gestation period, the following major changes were observed. Red blood cell counts, hemoglobin, and hematocrit increased slightly up to day 13

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
43
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 50 publications
22
43
2
Order By: Relevance
“…RBC, Hb and Ht decreased on Days 7, 14, 17 and 21 compared with non-pregnant rats, and the degree of decrease correlated with the course of pregnancy. These changes were consistent with the results of previous studies on pregnant rats (LaBorde et al, 1999;Papworth and Clubb, 1995;De Rijk et al, 2002;Kim et al, 2000;Katoh et al, 1992), rabbits (Wells et al, 1999), and womanemia, can be attributed to the normal plasma volume increase termed as hemodilution that occurs during pregnancy (Papworth and Clubb, 1995;De Rijk et al, 2002;Kim et al, 2000;Katoh et al, 1992;Baylis, 1980) and Table 1 to a decrease in the lifespan of erythrocytes (Lurie and Danon, 1992). Reticulocyte increased on Days 7, 14 and 17; this change might be a compensatory response to anemia; however, it was on the same level as that of non-pregnant -ciency anemia was induced in pregnant rats at the end of pregnancy, similar to pregnant women (Haram et al, 2001).…”
Section: Resultssupporting
confidence: 93%
“…RBC, Hb and Ht decreased on Days 7, 14, 17 and 21 compared with non-pregnant rats, and the degree of decrease correlated with the course of pregnancy. These changes were consistent with the results of previous studies on pregnant rats (LaBorde et al, 1999;Papworth and Clubb, 1995;De Rijk et al, 2002;Kim et al, 2000;Katoh et al, 1992), rabbits (Wells et al, 1999), and womanemia, can be attributed to the normal plasma volume increase termed as hemodilution that occurs during pregnancy (Papworth and Clubb, 1995;De Rijk et al, 2002;Kim et al, 2000;Katoh et al, 1992;Baylis, 1980) and Table 1 to a decrease in the lifespan of erythrocytes (Lurie and Danon, 1992). Reticulocyte increased on Days 7, 14 and 17; this change might be a compensatory response to anemia; however, it was on the same level as that of non-pregnant -ciency anemia was induced in pregnant rats at the end of pregnancy, similar to pregnant women (Haram et al, 2001).…”
Section: Resultssupporting
confidence: 93%
“…A variety of factors can affect the haematological and biochemical parameters of an animal, including breed, gender, diet, age, reproductive status and seasonal variations (Wells et al, 1999;Ozegbe, 2001). The haematological and biochemical parameters obtained in this study were within the normal ranges for rabbit species (Archetti et al, 2008;Özkan et al, 2012).…”
Section: Haematological Findingssupporting
confidence: 65%
“…On the other hand, Wells et al (1999) reported a decrease in TP and albumin in pregnant rabbits, and this is thought to reflect an increased blood volume.…”
Section: Haematological Findingsmentioning
confidence: 98%
“…Plasma triglycerides (TG) decreased at D 22 then increased at D 30 and even more after parturition. For Wells et al (1999), this parameter measured in the plasma of New Zealand female rabbits increases at D 19 and decreases until D 28 whereas Montoudis et al (1999) demonstrated a reduction in plasma TG content at D 22 followed by an increase at the end of gestation. Cholesterol decreased significantly at the 22 nd day of gestation and it increased in post-partum plasma.…”
Section: Quantification Of Matrix Metalloproteinases Mmp-2 and Mmp-9 mentioning
confidence: 94%